Limited simultaneous nitrification-denitrification (SND) in aerobic granular sludge systems treating municipal wastewater: Mechanisms and practical implications - Manuel Layer (Water Research X, 2020)
Simultaneous nitrification-denitrification (SND) is, in theory, a key advantage of aerobic granular sludge systems over conventional activated sludge systems. But practical experience and literature suggests that SND and thus total nitrogen removal are limited during treatment of municipal wastewater using AGS systems. This study thus aims at quantifying the extent and understanding the mechanisms of SND during treatment of municipal wastewater with aerobic granular sludge (AGS) systems. Experiments (long-term and batch-tests) as well as mathematical modelling were performed. Our experimental results demonstrate that SND is significantly limited during treatment of low-strength municipal wastewater with AGS systems (14–39%), while almost full SND is observed when treating synthetic influent containing only diffusible substrate (90%). Our simulations demonstrate that the main mechanisms behind limited SND are (1) the dynamics of anoxic zone formation inside the granule, (2) the diffusibility and availability of electron-donors in those zones and (3) the aeration mode. The development of anoxic zones is driven by the utilisation of oxygen in the upper layers of the granule leading to transport limitations of oxygen inside the granule; this effect is closely linked to granule size and wastewater composition. Development of anoxic zones during the aerobic phase is limited for small granules at constant aeration at bulk dissolved oxygen (DO) concentration of 2 mgO2 L−1, and anoxic zones only develop during a brief period of the aerated phase for large granules. Modelling results further indicate that a large fraction of electron-donors are actually utilised in aerobic rather than anoxic redox zones – in the bulk or at the granule surface. Thus, full SND cannot be achieved with AGS treating low strength municipal wastewater if a constant DO is maintained during the aeration phase. Optimised aeration strategies are therefore required. 2-step and alternating aeration are tested successfully using mathematical modelling and increase TN removal to 40–79%, without compromising nitrification, and by shifting electron-donor utilisation towards anoxic redox conditions.